THE IMPACT OF CLASSROOM MANAGEMENT STRATEGIES ON READING INTEREST AND READING ALOUD OUTCOMES IN GRADE 1 ELEMENTARY STUDENTS - Kurniawaty , Rochma; Daeng, Kembong; Devilla, Rego (Department of Educational Technology, Postgraduate Program, State University of Makassar, 2023)
All forms of teacher activities in the classroom as an effort to create and condition optimal classes so that teaching and learning processes occur are part of classroom management. There is a need to apply classroom management strategies so that student's interest in learning continues to increase. The purpose of this study was to describe the impact of classroom management strategies on cloud reading interest and aloud reading outcomes for grade 1 students of SD Inpres Mawang, Bontomarannu sub-district, Gowa Regency. This type of research is descriptive research using a qualitative approach. Utilizing interview tools and documentation, data collection techniques included observation. The subjects in this study were social studies teachers and students taking social studies subjects at SD Inpres Mawang, Bontomarannu sub-district, Gowa Regency. The results found in this study are: 1) Class management strategies for students' cloud reading interest, namely by carefully preparing all learning tools in the form of lesson plans and using various learning methods, and bringing students into the real world so that reading becomes fun and not boring so that it achieves the purpose of learning. 2) The implementation of class management on students' cloud reading interest is for the teacher to use a variety of reading methods, continue to develop appropriate learning models, and be ready to help students so that student's interest in reading increases and maximum results are achieved. 3) Obstacles and class management efforts towards students' cloud reading interest are during the last hour of learning and are constrained in terms of limited media provision, which causes student's interest in cloud reading to decrease.